Mature Cystic Teratoma with Gliomatosis Peritonei - Ching-Yu Chou; Wen-Fang Cheng; Chin-An Chen (Taiwanese Journal of Obstetrics & Gynecology, 2005)
Objective: Mature cystic teratoma with gliomatosis peritonei is an uncommon condition, with the implantation of nodules of mature glial tissue within the peritoneal cavity, which may be mistaken for peritoneal carcinomatosis or peritoneal tuberculosis. Here, we present a case of mature cystic teratoma with mature gliomatosis peritonei. Case Report: A 36-year-old woman had been suffering from progressive abdominal distension for 2 months. Sonography revealed a heterogeneous echo-complex mass measuring 15 × 12.7 × 10 cm in the pelvis. Computed tomography scan revealed a pelvic mass with calcification in the peritoneal cavity. A right ovarian tumor was found at laparotomy, and right salpingo-oophorectomy was performed. Miliary tumors were also noted on the omentum and peritoneal surfaces. Omentectomy and peritoneal biopsy were performed. The pathology report showed a mature cystic teratoma with mature gliomatosis peritonei. The patient was followed-up for 1 year, with no evidence of recurrence up to the time of writing. Conclusion: Gliomatosis peritonei is considered to be a benign lesion accompanying cystic teratoma. Extensive sampling is essential to exclude the presence of immature elements, which may imply a poor prognosis and require aggressive therapy.